2009
DOI: 10.1109/tgrs.2009.2023667
|View full text |Cite
|
Sign up to set email alerts
|

Surface Emissivity of the Arctic Sea Ice at AMSR-E Frequencies

Abstract: Surface emissivity is an essential quantity to retrieve surface and atmospheric parameters from satellite measurements. The surface emissivity of the Arctic sea ice is calculated using Advanced Microwave Scanning Radiometer-Earth Observing System (AMSR-E) radiance. The method accounts for the variation of the penetration depth in the snow-covered ice with frequency, air temperature, and sea-ice temperature. The variation of emissivity for different frequencies at different seasons is noticed, together with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 15 publications
4
34
0
1
Order By: Relevance
“…The penetration depths for the above‐mentioned microwave frequencies derived by for first‐year sea ice, multiyear sea ice, and snow with liquid water contents of 1% and 2% can be seen in Table 2. Similar penetration depths for first‐ and multiyear ice have been found by Mathew et al [2009].…”
Section: Theorysupporting
confidence: 92%
“…The penetration depths for the above‐mentioned microwave frequencies derived by for first‐year sea ice, multiyear sea ice, and snow with liquid water contents of 1% and 2% can be seen in Table 2. Similar penetration depths for first‐ and multiyear ice have been found by Mathew et al [2009].…”
Section: Theorysupporting
confidence: 92%
“…[]. Results for the extreme snow cases showed that depletions are not much discernible from results in Table , confirming that the snow depth over the Arctic sea ice is generally thin enough to ignore the snow impact at lower MW frequencies [ Andersen et al , ; Mathew et al , ].…”
Section: Emissivity Retrieval From Lower Frequency Microwave Measuremsupporting
confidence: 78%
“…The obtained emissivities were used for simulating AMSR‐E brightness temperatures. Mathew et al [] retrieved the sea ice emissivities from AMSR‐E measurements with the use of ice temperature regressed from near surface temperature of ERA‐Interim data and atmospheric correction, for the seasonal ice at one region and for multiyear ice at another region in January 2005. These values are used for generating interchannel emissivity correlations which are important factor in data assimilation.…”
Section: Resultsmentioning
confidence: 99%
“…The study by [30] shows that, at 36 GHz and higher frequencies, the emissivity of the snow/ice pack increases to values above 0.9, compared with values around 0.8 for dry snow and 0.6 for frozen crust. A relevant finding was concluded by [31], who estimated emissivity of Arctic sea ice using AMSR-E data. The authors reported an increase in MYI emissivity and a drop of FYI emissivity with high variability during summer months when ice surface or snow cover starts to melt.…”
Section: Misclassification Of Myi In Autumnmentioning
confidence: 85%